Determinants of Going Concern Audit Opinion Acceptance in Property and Real Estate Companies on the Indonesia Stock Exchange (IDX) - I Made Arya Wirasena; Merlyana Dwinda Yanthi (Jurnal Akuntansi, 2026)
This study analyzes the likelihood of property and real estate companies listed on the Indonesia Stock Exchange (IDX) receiving a going concern audit opinion during 2020–2024. Financial conditions are proxied by profitability, liquidity, solvency, operating cash flow, and sales growth, with the audit committee as the moderator and firm size as the control. The sample was selected using purposive sampling, resulting in 58 companies. The analysis was performed using binary logistic regression and Moderated Regression Analysis (MRA). The test results show that profitability and liquidity have a negative effect on the acceptance of a going concern audit opinion, while solvency has a positive effect. Conversely, operating cash flow and sales growth did not show a significant effect. The audit committee was also not proven to moderate the relationship between financial condition and going concern audit opinions. These findings empirically provide a predictive framework for stakeholders and independent auditors to assess the going concern of companies in the highly volatile property and real estate sector. Further research is recommended to examine other factors and different sectors.